2015
DOI: 10.1002/dc.23270
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cost‐effectiveness of fine needle aspiration biopsy versus image‐guided biopsy, and open surgical biopsy in the evaluation of breast cancer in the era of affordable care act: A changing landscape

Abstract: This study confirms the comparative effectiveness of FNAB in the evaluation of patients with breast cancer and justifies serious endorsement of this procedure as the initial diagnostic sampling modality for its unique potential in rapid reporting and cost-saving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…CNB offers advantages in definitively diagnosing invasive carcinoma, assessing mammographically detected calcifications and assisting with proliferative lesions, but similarly to FNAB, it is a sampling device. CNB is more invasive, time consuming, has a higher rate of complications, and has a greater cost for both the biopsy equipment and the required histopathological laboratory processing and reporting [16, 21, 22]. There are reports of a risk of track seeding by carcinoma [23], and of a possible worse prognosis after CNB [24].…”
Section: Introductionmentioning
confidence: 99%
“…CNB offers advantages in definitively diagnosing invasive carcinoma, assessing mammographically detected calcifications and assisting with proliferative lesions, but similarly to FNAB, it is a sampling device. CNB is more invasive, time consuming, has a higher rate of complications, and has a greater cost for both the biopsy equipment and the required histopathological laboratory processing and reporting [16, 21, 22]. There are reports of a risk of track seeding by carcinoma [23], and of a possible worse prognosis after CNB [24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our negative predictive value needs to be considered in that context, as we are uncertain of the outcomes in those for whom we lost contact. Poor compliance has been demonstrated consistently in the literature and remains a significant problem. Any patient unable or unwilling to undergo periodic follow‐up evaluation is not an appropriate candidate for surveillance and should undergo immediate biopsy.…”
Section: Discussionmentioning
confidence: 73%
“…Another cost‐effective method of addressing probably benign masses is fine needle aspiration biopsy (FNAB) . According to 2017 published Medicare reimbursement rates, image‐guided breast FNAB would cost $299.31 (codes 10022 and 88173).…”
Section: Discussionmentioning
confidence: 99%
“…59 In a recent comprehensive cost analysis of cancer detection in breast lesions, Masood et al demonstrated that the total cost to the patient (median biopsy cost and total hospital/pathology charges) for a palpable FNA ($522.64) was less than that for ultrasound-guided FNA ($3818.00) or for imageguided CNB ($5946.00), interestingly with somewhat comparable cancer detection rates across the procedures. 60 These relative costs appear to hold true in other organ systems as well. In a 2015 study of palpable neck nodules, Ryu et al quoted a cost of $19.90 for FNA, $243.10 for ultrasound-guided FNA, and $274.60 for ultrasoundguided CNB.…”
Section: Cost Considerations Of Fna and Cnbmentioning
confidence: 96%
“…An older 2008 study from Finland demonstrated that for breast lesions, palpable FNA cost less than palpable CNB (€36.51 vs €70.02), ultrasound‐guided FNA cost less than ultrasound‐guided CNB (€44.65 vs €82.94), and all were much less expensive than stereotactic‐guided CNB (€246.37) . In a recent comprehensive cost analysis of cancer detection in breast lesions, Masood et al demonstrated that the total cost to the patient (median biopsy cost and total hospital/pathology charges) for a palpable FNA ($522.64) was less than that for ultrasound‐guided FNA ($3818.00) or for image‐guided CNB ($5946.00), interestingly with somewhat comparable cancer detection rates across the procedures . These relative costs appear to hold true in other organ systems as well.…”
Section: Introductionmentioning
confidence: 99%